2009
DOI: 10.1242/jeb.034074
|View full text |Cite
|
Sign up to set email alerts
|

The freshwater Amazonian stingray, Potamotrygon motoro, up-regulates glutamine synthetase activity and protein abundance, and accumulates glutamine when exposed to brackish (15‰) water

Abstract: SUMMARYThis study aimed to examine whether the stenohaline freshwater stingray, Potamotrygon motoro, which lacks a functional ornithine-urea cycle, would up-regulate glutamine synthetase (GS) activity and protein abundance, and accumulate glutamine during a progressive transfer from freshwater to brackish (15‰) water with daily feeding. Our results revealed that, similar to other freshwater teleosts, P. motoro performed hyperosmotic regulation, with very low urea concentrations in plasma and tissues, in freshw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…Glutamine formation plays a major role in detoxifying exogenous and endogenous ammonia in non-ureogenic fishes, especially in the brain, during exposure to exogenous/environmental ammonia (Arillo et al, 1981; Dabrowska and Wlasow, 1986; Mommsen and Walsh, 1992; Peng et al, 1998; Lim et al, 2004a; Ip et al, 2005a; Veauvy et al, 2005; Wee et al, 2007; Wright et al, 2007; Tng et al, 2009; Sanderson et al, 2010) or after feeding (Wicks and Randall, 2002; Lim et al, 2004b). In certain fish species, like the swamp eel, M. albus (Tok et al, 2009), and the Amazonian freshwater stingray, Potamotrygon motoro (Ip et al, 2009), glutamine synthesized from endogenous ammonia can act as an important osmolyte for cell volume regulation during acclimation to high salinity. As for ureogenic and ureosmotic fishes, glutamine can act as a substrate for the synthesis of urea which is essential for osmoregulation in a hyperosmotic environment.…”
Section: Passage Of Proton-neutral Nitrogenous Compounds Across Mitocmentioning
confidence: 99%
“…Glutamine formation plays a major role in detoxifying exogenous and endogenous ammonia in non-ureogenic fishes, especially in the brain, during exposure to exogenous/environmental ammonia (Arillo et al, 1981; Dabrowska and Wlasow, 1986; Mommsen and Walsh, 1992; Peng et al, 1998; Lim et al, 2004a; Ip et al, 2005a; Veauvy et al, 2005; Wee et al, 2007; Wright et al, 2007; Tng et al, 2009; Sanderson et al, 2010) or after feeding (Wicks and Randall, 2002; Lim et al, 2004b). In certain fish species, like the swamp eel, M. albus (Tok et al, 2009), and the Amazonian freshwater stingray, Potamotrygon motoro (Ip et al, 2009), glutamine synthesized from endogenous ammonia can act as an important osmolyte for cell volume regulation during acclimation to high salinity. As for ureogenic and ureosmotic fishes, glutamine can act as a substrate for the synthesis of urea which is essential for osmoregulation in a hyperosmotic environment.…”
Section: Passage Of Proton-neutral Nitrogenous Compounds Across Mitocmentioning
confidence: 99%
“…An alternative explanation is that in cold smelt livers, GS may be upregulated as part of the general stress response and may serve to store nitrogen for biosynthesis (e.g., nucleotides and amino acids) in the spring. GS transcript levels were upregulated in liver of long-jaw mudsucker exposed to hypoxia (Gracey et al 2001), GS activities and protein levels were upregulated in liver of freshwater Amazonian stingray exposed to brackish water (Ip et al 2009), and GS transcript and protein levels were upregulated in liver of gulf toadfish during confinement stress (Kong et al 2000). Two glucocorticoid response elements were identified in the promoter region of the GS gene of gulf toadfish (Esbaugh and Walsh 2009), consistent with the contention that an increase in glutamine is a general stress response.…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
“…Recently, Wong et al (2013) demonstrated that H. signifer might experience greater salinity-induced oxidative stress in fresh water than in brackish water, possibly related to its short history of fresh water invasion. In the laboratory, H. signifer can survive in fresh water (salinity 0.7) indefinitely or in brackish water (salinity 20) for at least two weeks (Tam et al, 2003; Ip et al, 2009). Unlike potamotrygonid stingrays, it possesses a functional urea cycle (Ip et al, 2003; Tam et al, 2003), despite having relatively low plasma urea concentrations (45–70 mmol l −1 ) in fresh water.…”
Section: Introductionmentioning
confidence: 99%